Gambaran pengetahuan dan sikap guru di SMA Katolik Rex Mundi Manado tentang dampak kekerasan seksual terhadap perempuan - Moningkey, Chita Vithea Shella; Sapulete, Margareth; Ottay, Ronald (UNIVERSITAS SAM RATULANGI, 2016)
Objective: To reveal the overview of knowledge and outlook of teachers from Rex Mundi Catholic Senior High School in Manado about the outcomes of sexual violence against woman.Design: This is a qualitative descriptive research using Focus Group Discussion (FGD) to explore the participants knowledge and outlook, and in depth to obtain deep and independent informations about the focused research issue. Location of study was at Rex Mundi Catholic Senior High School in Manado. There were 11 constant teachers of Rex Mundi Catholic Senior High School with the average age of 26 to 58 years old and variety period of teaching experience. All of them were participated in the FGD and seven was picked for the in depth interview.Results: Informants devided the violence against woman in two types: physical and non physical. Knowledge about the variety form of sexual violence was mininal. They claimed that sexual violence is when rape occurs only. Victims are at risk of physical, mental and social impairment. School will perform specific approaches towards students who are victims and perpetrators of sexual violence. Conclusion: The research shows that the informants already had sufficient knowledge about violence against woman in general, but still have lack of knowledge about the sexual violence in particular. However, informants reveal critical outlook about teachers role in screening for sexual violence victims among students. On the other hand, the school s role in overcoming the outcomes of sexual abuse against students is limited by the school s regulations.